Georgia Public Expenditure and Financial Accountability Performance Assessment : Municipality Synthesis Report - World Bank Group (World Bank, Washington, DC, 2018)
The purpose of this PEFA assessment synthesis report is to provide an objective analysis of the present performance of the PFM system in Georgia’s municipalities using PEFA indicators. The synthesis report provides a collective assessment of PFM in three municipalities assessed by the World Bank funded by the European Union, plus twelve municipalities assessed with support from GIZ. These assessments used the 2016 PEFA methodology but only the three assessments by the World Bank followed the PEFA CHECK quality assurance process. The field assessments by the World Bank, which covered financial years 2015-2017, were done in May-June 2018 with PEFA CHECK issued by the PEFA Secretariat on October 23, 2018. With regard to the twelve municipalities assessed by GIZ, ten were assessed in 2017 and two in 2018.